Accuracy of pre-hospital trauma triage and field triage decision rules in children (P2-T2 study): an observational study. (April 2020) - van der Sluijs, Rogier; Lokerman, Robin D; Waalwijk, Job F; de Jongh, Mariska A C; Edwards, Michael J R; den Hartog, Dennis; Giannakópoulos, Georgios F; van Grunsven, Pierre M; Poeze, Martijn; Leenen, Luke P H; van Heijl, Mark; ,
Summary: Background: Adequate pre-hospital trauma triage is crucial to enable optimal care in inclusive trauma systems. Transport of children in need of specialised trauma care to lower-level trauma centres is associated with adverse patient outcomes. We aimed to evaluate the diagnostic accuracy of paediatric field triage based on patient destination and triage tools. Methods: We did a multisite observational study (P2-T2) of all children (aged <16 years) transported with high priority by ambulance from the scene of injury to any emergency department in seven of 11 inclusive trauma regions in the Netherlands. Diagnostic accuracy based on the initial transport destination was evaluated in terms of undertriage rate (ie, the proportion of patients in need of specialised trauma care who were initially transported to a lower-level paediatric or adult trauma centre) and overtriage rate (ie, the proportion of patients not requiring specialised trauma care who were transported to a level-I [highest level] paediatric trauma centre). The Dutch National Protocol of Ambulance Services and Field Triage Decision Scheme triage protocols were externally validated using data from this cohort against an anatomical (Injury Severity Score [ISS] ≥16) and a resource-based reference standard. Findings: Between Jan 1, 2015, and Dec 31, 2017, 12 915 children (median age 10·3 years, IQR 4·2–13·6) were transported to the emergency department with injuries. 4091 (31·7%) patients were admitted to hospital, of whom 129 (3·2%) patients had an ISS of 16 or greater and 227 (5·5%) patients used critical resources within a limited timeframe. Ten patients died within 24 h of arrival at the emergency department. Based on the primary reference standard (ISS ≥16), the undertriage rate was 16·3% (95% CI 10·8–23·7) and the overtriage rate was 21·2% (20·5–22·0). The National Protocol of Ambulance Services had a sensitivity of 53·5% (95% CI 43·9–62·9) and a specificity of 94·0% (93·4–94·6), and the Field Triage Decision Scheme had a sensitivity of 64·5% (54·1–74·1) and a specificity of 84·3% (83·1–85·5). Interpretation: Too many children in need of specialised care were transported to lower-level paediatric or adult trauma centres, which is associated with increased mortality and morbidity. Current protocols cannot accurately discriminate between patients at low and high risk, and highly sensitive and child-specific triage tools need to be developed to ensure the right patient is transported to the right hospital. Funding: The Netherlands Organisation for Health Research and Development, Innovation Fund Health Insurers.